Health care in resignifying life before a disease - Selli, Lucilda; Roque Junges, José; Meneghel, Stela; Vial, Eloir Antonio (O Mundo da Saúde, 2008)
This article theorizes on the role of professional care before the necessity of resignifying life of people suffering from an illness. The hegemony of the current model of health professionals training cancels the broad dimension of care. This work points to the reflective character of a humanist culture integrated to scientific knowledge as an element that faces the hegemonic model in health, characterizes a way to do health-promoting actions, and influences the said resignification.